Valorization of Kintamani Arabica Coffee Pulp as a Functional Food Ingredient: Integrating Environmental Risk Reduction and Antioxidant Potential - I Gusti Agung Yogi Rabani RS; Ardhinata Antares; Ida Ayu Agung Prawitasari; I Nyoman Arya Maha Putra (Jurnal Pijar MIPA, 2026)
The increasing production of Arabica coffee in the Kintamani region, Bali, has led to a proportional rise in coffee pulp waste, which remains inadequately managed. This study aims to evaluate the potential of Kintamani Arabica coffee pulp as a functional food raw material while simultaneously assessing its role in environmental risk mitigation through a zero-waste approach. Laboratory experiments were conducted to determine total phenolic content and antioxidant activity using the DPPH method, while a semi-quantitative Environmental Risk Assessment (ERA) was applied to evaluate pollution risks associated with coffee pulp disposal. The results demonstrated that coffee pulp contains phenolic bioactive compounds with very strong antioxidant activity (IC₅₀ = 13.96 ppm), comparable to established antioxidant-rich agricultural by-products. From an environmental perspective, converting coffee pulp into cascara (coffee pulp tea) reduced odor-related gas emission and groundwater contamination risks from high to low categories, achieving an overall risk reduction exceeding 75%. This study uniquely integrates functional food characterization with environmental risk assessment, providing scientific evidence that coffee pulp valorization supports circular economy strategies and sustainable coffee production systems.